Antioxidants in Hypoxic Ischemic Encephalopathy - Rathee, AVS; Prasad, PL (Journal of Nepal Paediatric Society, 2015)
Introduction: Perinatal asphyxia and related injuries are leading cause of morbidity and mortality in India. These babies are at risk to develop hypoxic ischemic encephalopathy (HIE) due to multiple organ including brain damage. The role of malondialdehyde (MDA) as a marker of free radical injury has been well established. Vitamin C and alpha Tocopherols have neutralizing effects on the free radicals. Considering these facts, it was decided to estimate serum MDA level in cases of HIE and the neutralizing effects of Vitamin C and Vitamin E. Material and Methods: The study was conducted in a tertiary care teaching hospital. Neonates with an Apgar score of <6 at 5 minutes and birth weight >2500g were included in the study. They were randomized into two groups. One group was given Vit E and vitamin C and the other was not given any of the anti oxidants. Serum MDA level were measured in both groups. Result: Serum MDA level was found to be increasing in both groups, but the increase was significantly higher in group II where antioxidants were not given. It was also found that serum MDA level was significantly low in antioxidants groups with HIE than those without antioxidants. Conclusion: Antioxidants supplementation in cases of HIE is associated with lesser production of free radicals and their neutralization is affected by antioxidants resulting into lesser damage to brain. DOI: http://dx.doi.org/10.3126/jnps.v34i3.10122 J Nepal Paediatr Soc 2014;34(3):171-174.